THE FUNCTIONS OF IDIOMS WITH MAGICAL TERMINOLOGY IN BUILDING THE STORY OF J. K. ROWLING’S “HARRY POTTER AND THE ORDER OF THE PHOENIX” - Haris Fadhillah; J Bismoko (Department of Applied Linguistics, Graduate School of Universitas Negeri Yogyakarta, 2014)
This study describes the functions of idioms with magical terminology in Harry Potter and the Order of the Phoenix in building the story. This study analyzed the novel from the linguistics perspective. The idioms with magical terminology found in the novel were compared to real English idioms. Comparison was done word by word and also to the context of the story. The analysis was also done by comparing words’ meaning and the semantic features. Finally the data were analyzed with related theories of linguistics and discourse analysis. The results of this study can be used as a consideration in teaching cultural relevancy in language teaching from the linguistic point of view in a novel. Keywords: functions of idioms, Harry Potter and the Order of the Phoenix, cultural relevancy in language teaching